Employer branding management in modern conditions - Li Haifeng (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the employer brand management process. The subject of research includes theoretical, methodological, and practical approaches to managing the employer brand of banking institutions. The purpose of the master's thesis is to develop and substantiate theoretical, methodological, and practical provisions for effectively managing the employer brand in modern conditions. The obtained results have significant practical value, as the theoretical provisions and conclusions of the study have been transformed into methodological developments and practical recommendations that banking institutions can apply to improve their employer brand management systems. This study emphasizes the strategic importance of employer branding as a tool for gaining a competitive edge in the labor market and ensuring organizational resilience under dynamic conditions. By integrating theoretical insights with practical solutions, it provides a comprehensive framework for effective employer brand management in banking institutions.
Scientific advisor: Morozova N., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; employer brand; employer brand management; competitiveness; improving the efficiency of the company